Mental Health Screening of the Elderly in a Social Nursing Home - Masrina Naomi; Novida Nengsih (UNUSA Press, 2026)
Elderly people are a vulnerable group at risk of experiencing physical and mental health disorders due to the aging process, which causes a decline in bodily functions and psychological abilities. Emotional mental disorders in the elderly, such as anxiety, depression, loneliness, and dementia, can affect quality of life and the level of independence in carrying out daily activities. Therefore, early detection through mental health screening is an important preventive step to identify the risk of mental disorders from the beginning. This activity aims to determine the emotional mental health condition of the elderly through screening using the Self Reporting Questionnaire (SRQ). The method used was a community service activity with a mental health screening approach involving 34 elderly people at the Panti Sosial Tresna Werdha Budi Luhur Jambi. The implementation was carried out over one day using the SRQ questionnaire consisting of 20 questions with “yes” and “no” answer choices. The screening results showed that most of the elderly were not indicated to experience emotional mental disorders, totaling 26 people (76%), while 8 people (24%) were indicated to experience emotional mental disorders. The majority of respondents were male, totaling 24 people (71%). These results indicate that mental health screening can serve as a preventive effort to increase elderly awareness of the importance of maintaining mental and physical health. In addition, increasing physical activity, religious activities, and relaxation techniques such as yoga and meditation can be strategies to prevent and reduce emotional mental disorders in the elderly. Thus, routine mental health screening needs to be carried out as part of elderly healthcare services to improve their quality of life and psychological well-being.